The crash energy absorption of the vehicles front structures - Griškevičius, Paulius; Žiliukas, Antanas (Transport, 2003)
During the frontal crash the longerons absorb most energy of all vehicles construction elements. In order to analyse the energy absorbing capabilities of longerons under axial compression loading and to evaluate the influence of longerons geometrical characteristics and materials degradation on the vehicles safety experimental investigations and numerical calculations were performed. To assess the crashworthiness of longerons the main objective was to study the behaviour of thin-walled structural elements under axial loading conditions using the Finite Element (FE) model. The numerical FE models were created using the computer code LS-DYNA. Two models of longerons were investigated with different sections shape and for each of them materials with the four different mechanical characteristics were applied. Validation of created FE model was performed according to the experimental investigation and the results were obtained of validated FE models of vehicles crash analysis [1]. The results of analyses show that the value of absorbed energy by the longerons of new vehides exceeds the value of the oldest cars. The degradation of structures in the old cars has the significant influence on the absorbed energy.First Published Online: 19 Dec 2011